Biological activities of pineapple (Ananas comosus L. Merr. var. Josaphine) vinegar in vitro and in vivo - Mohamad, Nurul Elyani (2016)
Improper handling of work stress, diet and lifestyle cause imbalance to the biological system in our body and led to various diseases nowadays. The number of patients with chronic diseases such as cardiovascular disease and cancer have increased greatly and becoming a major public health concern. The current treatment approaches are unfavorable due to the unwanted side effects observed. Natural resources such as fruits and vegetables contain antioxidants, minerals and vitamins that may help to prevent diseases and enhance the immune system. Vinegar produced from carbohydrate sources, such as fruits and grains, contains not only acetic acid, but also other bioactive compounds such as polyphenolics, volatile compounds, and organic acids. The present study was carried out to investigate several biological activities such as immunomodulation, hepatoprotective,anti-tumor and anti-obesity activities of pineapple vinegar using in vitro and in vivo model. Assays such as anti-oxidant, real-time PCR, proteome, western blot and metagenomic analyses revealed the underlying mechanism of pineapple vinegar in all in vivo study. Through the in vivo toxicity study, it was shown that the tested concentrations of pineapple vinegar were not only safe to be taken continuously but they also helped to increase the antioxidant levels (FRAP and SOD) and immune response (CD4, CD8, IFNV and IL2) in normal mice model. Meanwhile, in vivo hepatoprotective study showed that pineapple vinegar was able to promote the recovery of paracetamol induced liver inflammation in mice due to its antioxidant activities. Through several in vitro cancer assays such as MIT, flow cytometry cell cycle analysis, Annexin V analysis and scratch assay, the anticancer effect of pineapple vinegar was also revealed. Further investigation on the chemopreventive effect using murine model was done to support the results of in vitro study. Results showed that the treatment by high concentration pineapple vinegar has significantly reduced the tumor weight through its anti-metastasis and anti-inflammatory activities. Additionally, in vivo anti-obesity study indicated the potential of pineapple vinegar as anti-obesity agent through the reduction of the body weight, regulation of several obesity related genes and proteins and its ability to alter the gut micobiota. In conclusion, oral administration of tested concentrations in all the in vivo studies proved clearly that pineapple vinegar confers hepatoprotective, anti-tumor and anti-obesity effects in dose dependent manner. This study signifies the potential of pineapple vinegar as a functional food for therapeutic purposes.